Travel Writing and the Integration of East-Central Europe: John Paget’s Hungary and Transylvania - Pellérdi, Márta (Hungarian Journal of English and American Studies, 2021)
John Paget’s travelogue from 1839, Hungary and Transylvania; with Remarks on their Condition, Social, Political, and Economical, makes a clear distinction between the Kingdom of Hungary and the Principality of Transylvania, both under Austrian rule at the time, and the rest of Eastern Europe. In terms of the variety and depth of the descriptions of the social, political, and economic conditions in the East-CentralEuropean country and province, Paget’s comprehensive and objective text stands out from the travelogues written about the region in the nineteenth century. This essay demonstrates that Hungary and Transylvania reveals the author’s intention to rediscover the history and culture of a neglected European nation who have attempted for centuries, successfully, and often unsuccessfully, to orient their politics toward the West rather than the East. It suggests that despite the occasional colonial discourse, Paget’s travelogue is an attempt to economically, politically, and culturally promote the integration of Hungary and Transylvania into the more “civilized” West. (MP)